ANALYSIS OF THE PERUVIAN FOREIGN POLITICAL VISION, FORMULATED BY AMBASSADOR CARLOS GARCÍA BEDOYA - Arteta Cano, Jesus Armando (2022)
The national security of a country has special emphasis on the promotion and protection of national interests, and within them the defense of sovereignty and territorial integrity, the democratic constitutional state of law, social peace and human rights are considered as such. . And to preserve them, it is necessary to have an agile diplomatic service, which through our representations located in different countries seeks to contribute to the effort to achieve national objectives, for the benefit of the people of Peru. Our Foreign Ministry is the oldest public institution in the State, and throughout its years of existence it has had distinguished diplomats who have served the Homeland well. There is no doubt that Ambassador Carlos García Bedoya Zapata is one of the most outstanding in our history, so it is important to know his work.